The Influence of Job Stress, Work Life Balance and Role Conflict on Employee Performance PT. X (Banking Company) - Lubis, Rizki Wiharni Az.; Siahaan, Elisabet; Sinulingga, Sukaria (The International Conference on Education, Social Sciences and Technology (ICESST), 2024)
This research aims to determine the influence of job stress, work life balance and role conflict on employee performance at PT. X (Banking Company). The number of research respondents was 110 people, the research population was employees of PT. X (Banking Company), and uses non-probability sampling techniques. Multiple linear regression was used in data analysis. Research findings show the influence of job stress (X1), work life balance (X2), and role conflict (X3) on employees performance at PT. X (Banking Company). This is indicated by the F-count value of 56.240 with a significance of 0.000 (<0.05).